Islamic Banking, Moral Order and a Just Social Order - Ahmad Mansur (Islamic Economics Journal, 2023)
Moral order is nothing more than natural order in which all living beings are bound to each other. All-natural beings or (nature) other than human beings have no choice and are not free to choose and to do whatever they want to, but to obey the law of their beings, their natural beings and natural law, they cannot do otherwise. They have to submit their beings (to act in accordance to their natural instincts) to the natural law or to divine pattern and divine will. God is not responsible for human acts, as human beings are endowed by free will, intellectual reasoning and are capable not only of recognizing good and evil acts, but also of legislating good laws to regulate their lives in accordance to natural law, divine pattern and divine will.This paper will discuss Islamic banking in which its existence cannot be separated from the religion of Islam. It has to act and to submit to the natural law or to divine pattern and divine will. Its operation and practice should meet the legality of Islamic law, even it must go beyond that by putting more emphasis on morality and virtue ethics. It should not merely be driven by instrumental reason (rationality), or determined by criteria of calculating the most economical application means such as of maximum efficiency, cost-benefit analysis, and maximum profit as its measure of success. Islamic banking has to think that its existence is part of larger order that is a cosmic order, a great chain of beings, in which the act of one being definitely affects other beings. So, there is no other way for Islamic banking, but to be ethical banking to submit itself to moral order and natural order to help support the realization of a just social order. A just social order means moral order in which without it, it leads to chaos, as the survival of society or nation is really dependant on morality and virtue ethics.